2021
DOI: 10.3390/ijms222011121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bone Regeneration in Different Forms of Bovine Bone Scaffolds with Recombinant Human Bone Morphogenetic Protein-2

Abstract: The aim of this study was to compare the bone regeneration ability of particle and block bones, acting as bone scaffolds, with recombinant human bone morphogenetic protein (rhBMP)-2 and evaluate them as rhBMP-2 carriers. Demineralized bovine bone particles, blocks, and rhBMP-2 were grafted into the subperiosteal space of a rat calvarial bone, and the rats were randomly divided into four groups: particle, block, P (particle)+BMP, and B (block)+BMP groups. The bone volume of the B+BMP group was significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Since lipid droplets are often associated with adipocytes [57], it is possible that adipogenesis was promoted by BMP-2. In agreement with these data, Seok et al reported increased adipogenesis by rhBMP-2 in demineralized bovine bone particles and blocks grafted into the subperiosteal space of a rat calvarial bone [58]. Furthermore, there is the hypothesis that adipogenesis in bone marrow mesenchymal stem cells (BMSCs), the precursor cells of pre-osteoblasts, is the default pathway in the absence of osteogenic stimuli [59].…”
Section: Intracellular Inclusions In Human Pre-osteoblasts After Long...mentioning
confidence: 66%
“…Since lipid droplets are often associated with adipocytes [57], it is possible that adipogenesis was promoted by BMP-2. In agreement with these data, Seok et al reported increased adipogenesis by rhBMP-2 in demineralized bovine bone particles and blocks grafted into the subperiosteal space of a rat calvarial bone [58]. Furthermore, there is the hypothesis that adipogenesis in bone marrow mesenchymal stem cells (BMSCs), the precursor cells of pre-osteoblasts, is the default pathway in the absence of osteogenic stimuli [59].…”
Section: Intracellular Inclusions In Human Pre-osteoblasts After Long...mentioning
confidence: 66%
“…Therefore, there were no significant differences in BV and BMD between the 6w and 16w block groups. As in our previous study, when rhBMP-2 was used with a block-type bone scaffold, it induced osteogenesis and adipogenesis and contributed to new bone regeneration with adipose tissue formation [ 15 ]. In contrast to its formation in the particle bone scaffold, adipose tissue was formed in the central area of the block bone scaffold and created a large vacant space.…”
Section: Discussionmentioning
confidence: 95%
“…Various scaffolds, such as collagen sponges, hydroxyapatite, and demineralized bovine bone, have been used as rhBMP-2 carriers [ 29 , 30 ]. In our previous in vivo study, rhBMP-2 was used with different forms of bone scaffolds, including particle- and block-type bovine bone, and adipose tissue and new bone formation were compared between the two groups [ 15 ]. When rhBMP-2 was used with bone particles, a void space was created between the space of the bone graft material and the newly formed bone; however, when rhBMP-2 was used with block bone, a void space was created in the central area of the scaffold [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations